Publication rate of abstracts on breast cancer presented at different scientific events in Brazil - Rahal, Rosemar Macedo Sousa; Nascimento, Sergio; Soares, Leonardo Ribeiro; Freitas-Junior, Ruffo (Mastology, 2020)
Introduction: Medical congresses allow scientific production to be appropriately disseminated and discussed. However, most of the scientific papers presented at medical congresses do not go on to be published in indexed journals. The present study aimed to characterize the abstracts presented at three different congresses on breast cancer held in Brazil, and to determine the publication rate of these three events. Methods: Observational, retrospective study, where the observation unit consisted of the scientific papers presented at the Brazilian Congress of Mastology (CBM), Jornada Paulista de Mastologia (JPM) and Brazilian Breast Cancer Symposium (BBCS) in 2017. Initially, we recorded all the abstracts of works presented at the event. Subsequently, the works were searched in digital databases (BIREME/LILACS and MEDLINE/PubMed) and in the respective resumes of the authors on the Lattes platform. Results: The study included 266 abstracts of scientific papers presented in the three selected events, of which 21 (7.9%) were published in an indexed journal. Most of these studies were conducted predominantly in public institutions (71.1%), located in the State of São Paulo (30.5%) and were presented in the form of a poster (77.8%). The publication rate from the BBCS, CBM and JPM was 13.4, 5.4 and 3.4%, respectively (p = 0.03). Considering the published articles, there was no difference in journal impact factor b etween t he congresses ( p = 0.49). “Mastology” was t he journal t hat received t he l argest number o f p ublications (n = 8; 38.1%). Conclusion: In 2017, less than 10% of the abstracts on breast cancer presented at Brazilian congresses were published in an indexed journal. Among the main specialty events in the country, the Brazilian Breast Cancer Symposium has a significantly higher publication rate.